Anotasi terhadap Kamuflase Keputusan Fiktif Positif dalam Sengketa Tindakan Faktual di Pengadilan Tata Usaha Negara - Pasaribu, David; Irene Cristna Silalahi (University Of Bengkulu Law Journal, 2026)
The idea of realizing a good and clean regime is currently a mirage. The fictitious positive concept that is expected to provide responsive public services is often not fulfilled by the government. In reality, this problem is perennial and has become a further problem in judicial institutions. Today, the understanding of positive fictitious is believed to be a form of transformation of the object of the case, namely factual actions. The crucial problems are the fundamental differences between factual actions in the form of passive actions and positive fictitious actions in the perspective of administrative law, their respective conceptions, and the reasoning of judges in deciding positive fictitious actions that are camouflaged in factual action cases. The study employs a doctrinal research method utilizing a casuistic-conceptual approach. The results show a wrong interpretation in the form of positive fictitious camouflage in factual action disputes at Peratun. The existence of Peratun serves to clarify the distinction between factual actions and positive fictitious decisions. Factual actions relate to real action (commission) and passive action (omission), while positive fictitious decisions lead to administrative decisions (KTUN). The differences include the basis for filing, process, and completion period. The author also analyzes the ruling on the inclusion of positive fictitious applications in factual action disputes, where the judge plays a role in restoring the true nature of factual actions through the decision.